(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-45-54 Introduction. The article reveals the significance of the research in enriching the theory of translation with new data on the trends in the recoding of a two-level model-the reconstruction of a literary concept, in particular the literary concept of MEDIEVAL LIFE. The purpose to determine the trends of translation by means of the Russian language of the nominative field of the model-reconstruction of the literary concept of MEDIEVAL LIFE in Walter Scott’s novel “Ivanhoe”. The material was the nominees of the nominative field of the literary concept of MEDIEVAL LIFE, identified in the text of Walter Scott’s novel “Ivanhoe”. Through the use of a set of methods: linguistic analysis of the text, the method of interpretation, the method of continuous sampling and the method of comparative analysis, a comparative model is created-a reconstruction of the literary concept of MEDIEVAL LIFE, represented in Walter Scott’s novel “Ivanhoe”. Research results, discussion. The specifics of constructing a two-level model-reconstruction of the nominative field of the literary concept of medieval life, represented in the conceptual sphere of the novel by V. Scott “Ivanhoe” are determined; the tendencies of transcoding of the nominees of the Englishlanguage model-reconstruction by means of the Russian language are established; a two-level comparative model-reconstruction of the literary concept of MEDIEVAL LIFE is presented. In conclu- sion we found that the model-reconstruction of the literary concept of MEDIEVAL LIFE consists of a number of submodels, among which two submodels are significant: the submodel of the subconcept OF ROWENA’s CHAMBERS and the submodel of the subconcept of the CHAMBERS of a RICH JEW, consisting mainly of single-component nominees, which are translated mainly asymmetrically. Key words: modeling, model, model-reconstruction, text, text model